1992
DOI: 10.1039/an9921700125
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of three analytical techniques for the determination of chromium(VI) in soil extracts

Abstract: Three different analytical techniques [Ir5-diphenylcarbazide spectrophotometry, chelating ion-exchange chromatography (Chelex-IOO), and ion-pairing reversed-phase high-performance liquid chromatography (RP-HPLC) combined with electrothermal atomic absorption spectrometry (ETAAS)] were critically evaluated for the determination of CrV1 in soil extracts. Spectrophotometry was not applicable t o the analysis of most soil extract samples owing t o its high limit of detection (LOD = 30 ng cm-3), and the possibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…The sample acidification carried out before the DPC addition prevents the solubilization of Cr(III) species, the releasing of Cr(III) from complexes or colloidal particles, or even the increase of Cr(VI) reduction by organic compounds in the sample (Sule et al, 1996). Studies showed that interferences from organically complexed Cr(III) species were almost negligible in soil extracts when non-acidified DPC was used, and more significant with acidified DPC (Milacic et al, 1992 (Clesceri et al, 1998), as well as the removal of organic compounds from the samples (Mulaudzi et al, 2002), have been proposed. Very few methods for Cr determination are based on the formation of Cr(III) complexes in aqueous solution, and this is probably due to the slow reaction rate of the strongly hydrated Cr(III) ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample acidification carried out before the DPC addition prevents the solubilization of Cr(III) species, the releasing of Cr(III) from complexes or colloidal particles, or even the increase of Cr(VI) reduction by organic compounds in the sample (Sule et al, 1996). Studies showed that interferences from organically complexed Cr(III) species were almost negligible in soil extracts when non-acidified DPC was used, and more significant with acidified DPC (Milacic et al, 1992 (Clesceri et al, 1998), as well as the removal of organic compounds from the samples (Mulaudzi et al, 2002), have been proposed. Very few methods for Cr determination are based on the formation of Cr(III) complexes in aqueous solution, and this is probably due to the slow reaction rate of the strongly hydrated Cr(III) ions.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most used colorimetric methods for the Cr(VI) andyor total chromium determination is based on the reaction of Cr(VI) with diphenylcarbazide (DPC) (Lynch et al, 1984;Andrade et al, 1985;Milacic et al, 1992;Sule et al, 1996;Clesceri et al, 2002;Mulaudzi et al, 2002;Giusti et al, 2005). The absorbance of the red -violet complex of unknown composition, formed at the pH range of 1.6 -2.2, is read at 540 nm (Clesceri et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…After leaching, Cr(VI) was determined by ion chromatography or extraction with a liquid anion exchange solution of Amberlite LA 2/MIBK. Among different analytical techniques developed or modified in our laboratory for the determination of Cr(VI) in a variety of sample matrices [21,22,23,24] anion-exchange fast protein liquid chromatography (FPLC) with AAS detection offered simultaneous determination of Cr(III) complexes and Cr(VI) [25]. The technique was successfully applied in speciation of Cr in plant sap [25] and in the investigation of oxidation-reduction processes of trace amounts of Cr in highly alkaline lime-treated sewage sludge samples [26].…”
Section: Introductionmentioning
confidence: 99%
“…Various separation techniques have been used for this purpose: electrodeposition [2], HPLC [3][4][5], sorption or ion exchange in a column [3,[6][7][8], selective evaporation in the graphite furnace [9]. The total Cr content can be determined after a reduction or oxidation procedure.…”
Section: Introductionmentioning
confidence: 99%